CPR knowledge in future physicians: evidence to strengthen undergraduate medical training - Peña-Pinedo, Gustavo; Hernández-Patiño, Iván (Frontiers in Medicine, 2025)
IntroductionOut-of-hospital cardiac arrest (OHCA) is a leading cause of sudden death worldwide. In such cases, Cardiopulmonary Resuscitation (CPR), understood not only as chest compressions and ventilations but also as early recognition of cardiac arrest, activation of emergency services, and timely use of an Automated External Defibrillator (AED), is crucial for improving survival. These skills are especially important for medical students nearing the end of their academic training.ObjectiveTo assess adult CPR knowledge levels and associated factors among pre-medical students at a private university.MethodsObservational, analytical, and cross-sectional study. A validated virtual questionnaire based on the 2020 AHA guidelines was administered to 151 students in their 12th semester. General knowledge and domain-specific knowledge (cardiac arrest recognition, high-quality CPR, and AED use) were evaluated, along with their association with socioeeducational variables.ResultsOnly 41.06% demonstrated adequate CPR knowledge (mean score = 11.12/22). AED use was the most deficient domain (70.2% inadequate knowledge), followed by high-quality CPR (62.91%) and cardiac arrest recognition (60.93%). Female sex (aPR = 1.12; 95% CI: 1.01–1.26; p = 0.045) and prior completion of a Critical Patient course (aPR = 1.21; 95% CI: 1.07–1.35; p = 0.002) were significantly associated with higher knowledge. No significant associations were found with age, previous CPR training, or having healthcare worker relatives.ConclusionFewer than half of the pre-intern students possessed adequate adult CPR knowledge despite prior training. Integrating periodic, competency-based training (addressing cognitive, practical, and attitudinal dimensions) into medical curricula could strengthen these skills and ensure future physicians are prepared to save lives.